Compliance in amblyopia therapy: objective monitoring of occlusion. Issue 6 (June 1995) - Fielder, A R; Irwin, M; Auld, R; Cocker, K D; Jones, H S; Moseley, M J
Abstract : AIM/BACKGROUND–This study aimed to determine the feasibility of objective compliance monitoring of amblyopia therapy in clinical research. Occlusion has been the mainstay of amblyopia therapy for over 250 years, yet it has never been subjected to rigorous evaluation. Treatment regimens range arbitrarily from a few minutes to most of the waking hours of the day. Compliance is problematic and as, hitherto, accurate objective monitoring has been impossible it is not known how much occlusion is required to effect an improvement in vision. METHODS–An occlusion dose monitor (ODM) has been developed. The ODM consists of a modified occlusion patch and a miniature battery driven datalogger which periodically monitors patch skin contact. The patch is a standard disposable item with two miniature electrocardiogram electrodes attached to its undersurface. The datalogger comprises a high speed static RAM and a clock driven address counter. Data are retrieved using an IBM PC/AT computer. Fifteen child amblyopes were randomly allocated unilateral occlusion of 1, 4, or 8 hours per day for 4 weeks. Owing to data loss, presumed because of accumulation and discharge of static electricity, an additional child was included in the 8 hour group. Outcome measures were objective (ODM) and subjective (diary) compliance with treatment, logMAR visual acuity, and contrast sensitivity. RESULTS–Objective monitoring of occlusion is technically feasible and clinically informative. CONCLUSION–Objective monitoring of occlusion has opened up new research opportunities which, it is hoped, will enable the dose-effect relation of occlusion therapy in the various types of amblyopia to be investigated objectively, and facilitate the design of effective therapeutic regimens.